2021
DOI: 10.1080/10408436.2021.1935713
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive review on carbon nanotubes embedded in different metal and polymer matrix: fabrications and applications

Abstract: Carbonaceous material, especially carbon nanotubes (CNTs), have incredible exceptional properties, such as high thermal and mechanical stabilities, and good catalytic and adsorption capabilities. In recent years, hybrid nanocomposites have attained considerable attention due to the combination of unique organic and inorganic elements in a single material. Hence, these nanocomposites have been employed for various applications such as drug delivery, sensors, corrosion protection materials, flame retardant addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 238 publications
1
8
0
Order By: Relevance
“…Finally, we concluded various CNTbased nanostructures inserting to pristine polymeric samples cause mechanical improvement of them. Previously, similar reports have been published in experimental studies [31][32][33][34]. In these studies, researchers indicated the addition of CNT when properly mixed and aligned will increase the mechanical properties of pristine polymer-based matrixes.…”
Section: Mechanical Performance Of Reinforced Pu/cnt Samplesupporting
confidence: 59%
“…Finally, we concluded various CNTbased nanostructures inserting to pristine polymeric samples cause mechanical improvement of them. Previously, similar reports have been published in experimental studies [31][32][33][34]. In these studies, researchers indicated the addition of CNT when properly mixed and aligned will increase the mechanical properties of pristine polymer-based matrixes.…”
Section: Mechanical Performance Of Reinforced Pu/cnt Samplesupporting
confidence: 59%
“…The enhancement of CNT distribution in polymer matrix has been achieved using various methods, including melt processing, in situ polymerization, coagulation precipitation, and ultrasonic dispersion. [68][69][70] Another way to improve PVC and CNT compatibility is to acid functionalize CNT. Mkhabela et al developed PVC/phosphorylated multi-walled carbon nanotube (p-MWCNT) and PVC/ virgin-MWCNT composites using a melt processing approach.…”
Section: Frequency Peak (Cmmentioning
confidence: 99%
“…Various studies have been performed to discover effective fabrication routes to attain the finest, highly stable, and shape-controlled carbon nanotube-based nanocomposites, for instance, filling, hydrothermal, arc-discharge, chemical vapor deposition, and pyrolysis methods. In our previous work [131], a comprehensive discussion of different routes through which carbon nanotube-based nanocomposites can be developed along with their merits and demerits has been presented. Fig.…”
Section: 1mentioning
confidence: 99%